Relationship of Parity, Nutritional Status, Gestational Age with Hemoglobin Levels of Pregnant Women at Sukajadi Health Center in 2020 - Fariza Ayang Viamita; Sendy Pratiwi Ramadhani; Helni Anggraini (Institute of Computer Science (IOCS), 2022)
The World Health Organization (WHO), in 2016 reported that the prevalence of anemia in pregnant women in the world was around 40.1 percent. Based on the 2018 Riskesdas, the incidence of anemia in pregnant women in Indonesia is still high, at 48.9 percent of pregnant women who experience anemia. In 2013 the number of pregnant women who experienced anemia was 37.1 percent and increased in 2018 to 48.9 percent. This study was conducted to determine the relationship between parity, nutritional status, and gestational age with hemoglobin levels of pregnant women simultaneously at the Sukajadi Public Health Center in 2020. The results obtained were that there was a significant relationship between parityaand hemoglobin levels of pregnant women at the Sukajadi Public Health Center in 2020 with p value 0.001 and OR 4.672, for the relationship between nutritional status and hemoglobin levels of pregnant women at the Sukajadi Public Health Center in 2020 there is also a significant relationship with p value 0.000 and OR 56,667. And for the relationship between gestational age and hemoglobin levels of pregnant women at the Sukajadi Public Health Center in 2020 there is also a significant relationship with a p value of 0.005 and an OR of 3.661.